Role of cytokines in oral malignancies - Shabnam Unus; Sarangarajan Ramabadran; Preeti Lakshmi; Narasimham; Nandhini Gunasekaran; Rajkumar Krishnan (Wolters Kluwer Medknow Publications, 2014)
Cytokines are nonstructural proteins, which act as molecular messengers in the movement of various inflammatory cells, as well as in inducing growth and regeneration in the surrounding microenvironment. The inflammatory cytokine network, which influences growth, proliferation, and differentiation of cells in normal health and healing has also been found to induce tumorigenesis and tumor progression. A detailed study of the role of cytokines in various cancers has brought out many facts regarding the mechanisms and sequence of events that has eventually led to cancer. A study of these cytokines in tumorigenesis will throw further light on its usefulness in early detection of oral cancer and its potential as a therapeutic target in cancer therapy.